Toxicity Characterization, Detection and Remediation of Contaminants in Soils and Groundwater (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The toxicity levels of heavy metals, pesticides, herbicides, and antibiotics pose a significant threat to agricultural soil around the world, as well as human health and agricultural production. We aim to exploit phytoremediation and safe production technology for the remediation of heavy metals, pesticides, herbicides, and antibiotics, as well as establish these phytoremediation strategies as suitable options for the management of agricultural contaminated soils. Furthermore, the implimentation of these phytotechnologies in a sustainable, cost-effective, and safe manner has led to many benefits in the phytoremediation of agricultural contaminated sites, such as, for instance, the restoration of important ecosystem services, e.g., safe production, nutrient cycling, carbon storage, water flow regulation, erosion control, water purification, fertility maintenance, etc. This reprint will highlight the plant intercropping remediation mode, establishing phytoremediation technologies combined with agronomic measures and physical-chemical remediation to ensure safe production in agricultural contaminated soils.